Electrical conductivity anomalies in the contact zones of Archean and Proterozoic geobloks on the Ukrainian and Baltic Shields - I. Rokityansky; E. Yu. Sokolova; A. V. Tereshyn; A. G. Yakovlev; Working group LADOGA (Геофизический журнал, 2018)
Kirovograd (KA) and Ladoga (LA) anomalies of the crustal electrical conductivity are located in the Sarmatian and Fennoscandinavian domains of the East European Craton. In the paper the main attention is paid to the areas of anomalies, which are juxtaposed with the regional linear zones of Archean (AR) and Proterozoic (PR) geoblocks junction. For Fennoscandia, the analysis is based on data from the latest magnetotelluric (MTS) and magnetovariational (MVP) studies with emphasis on the anomalous fields of horizontal components of geomagnetic variations (tensor M). Comparison of the geoelectric parameters of the KA and LA reveals the prominent features of their similarities and differences. Both anomalies consist of two quasi-parallel conductors “А” and “Б”, distant one from another on 50—100 km. The main conductors “A” are located within megablocks of the PR age. They were detected by the anomalous behavior of geomagnetic variations (MVP method) and have a maximum frequency response of the MVP parameters (induction vectors and tensor M) at the periods T0 » 1 ¸ 2 thousand seconds, which gives the estimates of the total longitudinal conductance G » (1—3)×108 S×m for both KA and LA anomalies. Subparallel conductors “Б” produce extremal responses at higher frequencies (T0 » 100 ¸ 300 s) and are less conductive (G » (0,4—2)×107 S×m). Conductor “Б” directly marks the AR-PR border, which passes through regional faults: the Yanisyarvinsky on the Baltic Shield and the Krivorozhsko-Kremenchugsky on the Ukrainian Shield. Recent studies reveal the existence of Baryatinska anomaly of electrical conductivity on the western slope of the Voronezh massif which can be considered as the northern continuation of the КА up to 54,5° of northern latitude. The southern extension of the LA is the Ilmenska anomaly at the 58° of northern latitude, apparently running to 56° and having a branch, probably, extending up to the Baryatinska anomaly. These data give rise the hypotheses of the Trans-European submeridional chain of electrical conductivity anomalies (TECAE), stretching from the northern end of the Gulf of Bothnia to the Black Sea. We present geophysical materials supporting this assumption, with the most solid one being the general spatial coincidence of the TECAE with the gradient zones of the transcraton permanent magnetic field anomalies (PMFA), where the positive PMFA are located east of the electrical conductivity anomalies, and the negative ones are west of them.